Application Of Mamdani Fuzzy Logic To Predict Rice Pest Attacks On Bp3 Bingin Kuning - Reynaldi, Abdillah Ahmad; Sapri, Sapri; Beti, Ila Yati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The Agricultural and Fisheries Extension Centre (BP3) Bingin Kuning is an agricultural extension centre that carries out activities related to agricultural extension preparation, evaluation, management, and development across various sectors. Every year, BP3 Bingin Kuning collects data on temperature, humidity, rainfall, and the number of attacks by each type of pest that occurs. The application of Mamdani fuzzy logic to predict rice pest infestations at BP3 Bingin Kuning can help in obtaining information on rice pest infestations each year, serve as a basis for evaluating measures to address future pest infestations, and assist farmers in addressing potential pest infestations earlier, thereby supporting BP3 Bingin Kuning in its agricultural extension activities. Based on test data under conditions of 24°C temperature, 90% relative humidity, and 295 mm rainfall in 2024, the pest type with the highest predicted attack frequency is the Keong Mas pest. Based on the system testing conducted, it can be concluded that the functionality of the Mamdani fuzzy logic application for predicting rice pest attacks at BP3 Bingin Kuning is functioning well and capable of displaying pest attack prediction results in accordance with the stages of the Mamdani fuzzy logic system.